2021
DOI: 10.29121/ijetmr.v8.i9.2021.1015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leverage, Firm Size, and Sales Growth on Income Smoothing and Its Implication to the Firm Value (Study on State-Owned Companies Listed in Indonesia Stock Exchange 2016-2019)

Abstract: The purpose of this research was to determine the effect of leverage, firm size and sales growth on income smoothing and its implication to the firm value. The population used on this research was 24 state-owned companies listed on Indonesia Stock Exchange. The samples were determined using purposive sampling method and there were 19 companies which selected as the samples. The analytical method used on this research was statistic descriptive and panel data regression and use Eviews 9 for data processing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
3
1
1
Order By: Relevance
“…The results of this test confirm the findings of Indrawan & Damayanthi (2020), Oktaviasari et al (2018), Ramanel & Susuilo (2018), and Widhyawan & Dharmadiaksa (2015) although using different proxies. However, the result of this study is not in line with Arifah et al (2022), Bobby et al (2022), Mulyati & Mulyana (2021), Nathania & Nugroho (2023), Putri & Lutfillah (2020), Trisnawati et al (2017), and Tsuroyya & Astika (2017. Companies with higher debt have the desire to convince creditors that the company is in a stable condition.…”
Section: The Association Between Debt Policy and Income Smoothingcontrasting
confidence: 69%
See 1 more Smart Citation
“…The results of this test confirm the findings of Indrawan & Damayanthi (2020), Oktaviasari et al (2018), Ramanel & Susuilo (2018), and Widhyawan & Dharmadiaksa (2015) although using different proxies. However, the result of this study is not in line with Arifah et al (2022), Bobby et al (2022), Mulyati & Mulyana (2021), Nathania & Nugroho (2023), Putri & Lutfillah (2020), Trisnawati et al (2017), and Tsuroyya & Astika (2017. Companies with higher debt have the desire to convince creditors that the company is in a stable condition.…”
Section: The Association Between Debt Policy and Income Smoothingcontrasting
confidence: 69%
“…On the contrary, Arifah et al ( 2022) and Nathania & Nugroho (2023) found that debt policy is negatively associated with income smoothing. Furthermore, Bobby et al (2022), Mulyati & Mulyana (2021), Putri & Lutfillah (2020), Trisnawati et al (2017 and Tsuroyya & Astika (2017) suggested that debt policy is not associated with income smoothing. Thus, the various results of the previous studies boost to reexamine the association debt policy and income smoothing.…”
Section: Introductionmentioning
confidence: 98%
“…Firm Age (Fan & Wang, 2019) The age of the firm from its establishment until the year of observation. Firm Size (Hu & Sun, 2018) Ln Total Asset Growth Sales (Mulyati & Mulyana, 2021) Salest -Salest-1…”
Section: Methodsmentioning
confidence: 99%
“…Company managers receive more information as internal parties. So, managers are motivated to use this information for personal gain (Mulyati & Mulyana, 2021). Jensen and Meckling (1976) stated that agency theory is an agency relationship between one or more people giving authority to other parties in providing services or agents with the power to make decisions.…”
Section: Literature Review Agency Theorymentioning
confidence: 99%